Nutritional Status Effects the Age of Menarche - Esti Yunitasari; Retno Indarwati; Devi Rahma Sofia (Jurnal Ners, 2009)
Introduction: The improved nutritional status, which shown by increasing BMI and body fat percentage associated to a decrease in menarche's. This study was aimed to analyse correlation between the nutritional status with the age of menarche. Method:. Design used in this study was cross-sectional. Samples in this study were student at traditional muslim school and  were taken using purposive sampling, that was based  from inclusion and exclusion criteria. Data were analyzed using Spearman Rank Correlation with significance level  α ≤ 0.05. Result: The result showed that most (73%) of the students at traditional muslim boarding school had normal nutritional status. The majority of samples  got menarche at age > 13 years old. The result showed that there was correlation between nutritional status and age of menarche (p: 0.001).  It can be concluded that the girl’s muslim boarding school with better nutritional status got earlier the age of menarche. Discussion: It is recommended to do routine evaluation about nutritional status in muslim boarding school and to pay attention about consumption since early ages so the students at traditional muslim school would not get menarche in later time.